Beginning a Family and Adopting a Healthy Lifestyle : A Review of the Global Evidence - Moucheraud, Corrina; Hasan, Rifat (World Bank, Washington, DC, 2016)
Decisions during youth have great long-term impacts on human development, which is key to poverty alleviation and economic development. During adolescence, two of the primary transitions are beginning a family and adopting a healthy lifestyle. Youth face many choices and challenges around these key decisions, such as when to initiate sex, when to marry, when to have children, and whether to engage in risky behaviors – all of which affect their future health and future opportunities. Consequences of these early decisions can have long-lasting effects on adolescents and their communities, potentially increasing public health costs and depleting human capital. This note briefly presents program and policy approaches that have been implemented in different contexts for addressing these two key transition periods of youth: beginning a family and adopting a healthy lifestyle. It concludes by presenting a set of programmatic lessons and investment recommendations based on the global evidence.